Keberkesanan pendekatan islamic project© sebagai kaedah pengajaran dan pembelajaran terkini pendidikan akhlak dalam kalangan guru serta murid prasekolah kemas di negeri Kelantan - Mazeni, Ismail (2020)
Islamic Project © is a teaching and learning method built to inculcate the education of preschool children which includes manners in conversation, socializing and so on. The aim of this study is to develop and evaluate the effectiveness of the use of Islamic Project © methods by preschool teachers in helping them to improve the morale of preschool students in the Kelantan state. This study involves two research methods, quantitative and qualitative. This study involved three phases. The first phase involves analysis of past studies and analysis of research needs. The second phase is the construction phase of the Islamic-Project Module © based on the Delphi Modified Technique. The third phase is the evaluation phase. This phase involved 50 people from the intervention group and 50 from the control group. The effectiveness of the intervention was assessed using Kirkpatrick's 4-Level Rating Model. The results showed that the structure and content of this Islamic Project © module reached a very high level of satisfaction (CVI = 0.95). The ANCOVA analysis also showed that there was a significant difference in all comparisons between the intervention and control groups, where the mean of students’ knowledge is increased in the intervention group. The results also showed a significant increases in the change of attitude scores between the intervention and control groups over time (f-stat = 420.47, p-value = <0.001) and there was a significant increases in the change in practice scores between the intervention and control groups over time (f-stat = 112.20, p-value = <0.001). The teachers who have been interviewed also found that the module of Islamic Project ©, could enhance the learning through (1) investigation including asking questions, motivations, observations and discussions, (2) teamwork including, concern for each other and (3) communication including active communication, sharing, social interaction and storytelling. This Islamic Project © module has also been widely adopted in most KEMAS in Kelantan as an effective method of educating and nurturing morals among preschool students.